Achieving Continuity of Care: Facilitators and Barriers in Community Mental Health Teams - Belling, R; Whittock, M; McLaren, S; Burns, T; Catty, J; Jones, I; Rose, D; Wykes, T (2011)
Background: The integration of mental health and social services for people diagnosed with severe mental illness (SMI) has been a key aspect of attempts to reform mental health services in the UK and aims to minimise user and carer distress and confusion arising from service discontinuities. Community mental health teams (CMHTs) are a key component of UK policy for integrated service delivery, but implementing this policy has raised considerable organisational challenges. The aim of this study was to identify and explore facilitators and barriers perceived to influence continuity of care by health and social care professionals working in and closely associated with CMHTs.Methods: This study employed a survey design utilising in-depth, semi-structured interviews with a proportionate, random sample of 113 health and social care professionals and representatives of voluntary organisations. Participants worked in two NHS Mental Health Trusts in greater London within eight adult CMHTs and their associated acute in-patient wards, six local general practices, and two voluntary organisations.Results: Team leadership, decision making, and experiences of teamwork support were facilitators for cross boundary and team continuity; face-to-face communication between teams, managers, general practitioners, and the voluntary sector were facilitators for information continuity. Relational, personal, and longitudinal continuity were facilitated in some local areas by workforce stability. Barriers for cross boundary and team continuity were specific leadership styles and models of decision making, blurred professional role boundaries, generic working, and lack of training for role development. Barriers for relational, personal, and longitudinal continuity were created by inadequate staffing levels, high caseloads, and administrative duties that could limit time spent with users. Incompatibility of information technology systems hindered information continuity. Flexible continuity was challenged by the increasingly complex needs of service users.Conclusions: Substantive challenges exist in harnessing the benefits of integrated CMHT working to deliver continuity of care. Team support should be prioritised in terms of IT provision linked to a review of current models of administrative support. Investment in education and training for role development, leadership, workforce retention, and skills to meet service users' complex needs are recommended. © 2011 Belling et al; licensee BioMed Central Ltd.